Introduction: Tradition and Innovation in Franco-Belgian Bande dessinée. Issue 2 (1st September 2021) - Louwagie, Fransiska; Lambert, Simon
Abstract : This thematic issue arises from the symposium 'Tradition and Innovation in Franco-Belgian Bande dessinée ', held at the University of Leicester on 13 March 2020. Over three panels with a respective focus on 'Revisiting the Classics', 'Contemporary Perspectives', and 'Reshaping Franco-Belgian Bande dessinée ', the symposium brought out a variety of perspectives on contemporary bande dessinée and its links to the Franco-Belgian tradition. The symposium saw the participation of a range of international contributors, including early career scholars, faculty, and artist contributors, based in Greece, Switzerland, Portugal, Canada, Panama, Israel, and the UK. We would like to thank our speakers for their contributions as well as for their flexibility in revising travel arrangements and, in some cases, arranging online delivery at short notice, as the start of the COVID-19 pandemic was unfolding in their respective countries at the time of the event. Our particular thanks go to Laurence Grove from the University of Glasgow for his keynote intervention entitled 'The Relevance of Tintin', and to graphic novelist Michel Kichka, who gave a keynote talk about the Franco-Belgian influences in his own work as well as a public seminar on his graphic novel Deuxième Génération . We are grateful to Wallonia-Brussels International (WBI), the Association for the Study of Modern and Contemporary France (ASMCF), the Society for French Studies (SFS), and the School of Arts at the University of Leicester for their sponsorship of the keynote sessions, the conference participation of comics artist Ilan Manouach, and travel and registration bursaries for early career researchers. For this follow-up publication, we express our particular thanks to all contributors and peer-reviewers, to Wallonia-Brussels International for support to the translation, and to the editors of European Comic Art, for their kind and patient assistance.